Mixed regime in a quasi-linear system - Dinh, Nguyen Van; Chi, Tran Kim (Vietnam Journal of Mechanics, 2000)
A quasi-linear system with cubic nonlinearity under two external excitations in sub harmonic responses of order 1/2 and 1/3 was examined. In the system under consideration there appears mixed oscillation due to the interaction between derived excitations. Various forms of the resonance curve were identified. The stability study was based on an abbreviated form of the second stability condition [2].